1972
DOI: 10.1021/es60069a001
|View full text |Cite
|
Sign up to set email alerts
|

Energy dispersive x-ray fluorescence analysis of air particulates in Texas

Abstract: Standards made up from calibrated solutions deposited on filter paper and dried were measured along with the specimens and blanks. Analytical results were compared with those obtained by atomic absorption spectrophotometry. Air particulate pollution data from a statewide survey in Texas were compared with other available data. The method and equipment has proved itself capable of use for air particulate survey measurements and for pollution source location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

1975
1975
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 3 publications
0
11
1
Order By: Relevance
“…Before comparing data in Table 1, one irregularity in the Table will be discussed. The Cu levels both in Pittsburgh and the rural area appeared to be at least ten times higher than values reported previously (Rhodes et al, 1972;Granat et al, 1972;Gatz, 1972). This can be observed also in the comparison of ratios of Cu to other heavy elements in Pittsburgh rainwater and air particulate data.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Before comparing data in Table 1, one irregularity in the Table will be discussed. The Cu levels both in Pittsburgh and the rural area appeared to be at least ten times higher than values reported previously (Rhodes et al, 1972;Granat et al, 1972;Gatz, 1972). This can be observed also in the comparison of ratios of Cu to other heavy elements in Pittsburgh rainwater and air particulate data.…”
Section: Discussioncontrasting
confidence: 57%
“…Deviations will be up to 50% among different targets. Self absorption of the samples is considered theoretically according to the thin-specimen criterion (Rhodes et al, 1972):…”
Section: Atomic Numbermentioning
confidence: 99%
“…A working rule of thumb exists which states that absorption or enhancement effects will be negligible (i.e. less than 5%) when where µ is the total mass absorption coefficient for incident and transmitted radiation in cm 2 g −1 and M is the mass on the filter in g cm −2 16. It is therefore necessary to limit loadings of fume collected on membrane filters to generally less than 2 mg cm 2 and limit the lightest element analysed to Titanium.…”
Section: Resultsmentioning
confidence: 99%
“…Methods suitable for analysis of a wide range of elements by both wavelength and energy-dispersive methods have been reported. 259 - 260 Birks 261 has shown that sensitivity and detection limits in XRF analysis may be predicted theoretically, and that such predictions may be used to indicate the optimum instrumental parameters for the element and sample.…”
Section: / X-ray Emission Analysismentioning
confidence: 99%